Triangulasi Data Dalam Analisis Data Kualitatif - Nurfajriani, Wiyanda Vera; Ilhami, Muhammad Wahyu; Mahendra, Arivan; Afgani, Muhammad Win; Sirodj, Rusdy Abdullah (Jurnal Ilmiah Wahana Pendidikan, 2024)
The world of education as an incubator of ready-to-work personnel, really needs quality information to be used as reference material in the learning process and related to the information learning process itself. This research aims to discuss the triangulation research method. The method used is library research, data collection by finding sources and reconstructing from various sources such as books, journals, and existing research. Triangulation is a method used in qualitative research to check and establish validity by analysing from various perspectives. The purpose of using the triangulation method, is to get better results when compared to using only one method in a study.